1999
DOI: 10.1051/rnd:19990144
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor II (IGF-II) mRNA expression during skeletal muscle development of double-muscled and normal bovine foetuses

Abstract: -We investigated the IGF-II gene expression in developing Semitendinosus muscle in foetal normal and double-muscled cattle. Samples from normal and double-muscled foetuses ranging from 90 to 210 d post-conception were collected and total RNA extracted. Northern blot analysis was performed using the human IGF-II cDNA probe. Five 5.1, 4.4, 3.7, 2.6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Kocamis et al [21] showed that IGF-II mRNA levels were significantly higher in myostatin knockout mice soleus muscles with no translation in active myostatin than in those of control mice. We can thus hypothesise, that our previous results (more IGF-II mRNA in double-muscled animals where myostatin is inactive) [8] were in agreement with those of Kocamis et al (21) (more IGF-II mRNA in animals where there is no myostatin). It would have been interesting to discuss possible relations between IGF-II and GHR, but to our knowledge, no relation has been found in the literature between GHR mRNA abundance and the IGF-II mRNA level [33].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Kocamis et al [21] showed that IGF-II mRNA levels were significantly higher in myostatin knockout mice soleus muscles with no translation in active myostatin than in those of control mice. We can thus hypothesise, that our previous results (more IGF-II mRNA in double-muscled animals where myostatin is inactive) [8] were in agreement with those of Kocamis et al (21) (more IGF-II mRNA in animals where there is no myostatin). It would have been interesting to discuss possible relations between IGF-II and GHR, but to our knowledge, no relation has been found in the literature between GHR mRNA abundance and the IGF-II mRNA level [33].…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, these growth factors are known to play a role in muscle differentiation [7]. In addition, in a previous study, we showed that IGF-II mRNA were present in large amounts in foetal muscle cells [8].…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…In cattle, the IGF-I, IGF-II and insulin receptor concentrations were shown to decrease throughout foetal development from 3 to 5 months of age onwards in both the skeletal muscle (Boge et al, 1995;Listrat et al, 1999b) and the heart (Hocquette et al, 2006 for IGF-I and insulin receptors only). In various mammals, increase in IGF-I (Jensen et al, 2003 for humans) and IGF-II plasma levels (Listrat et al, 1999a for cattle) were observed throughout gestation. Therefore, the IGF-I, IGF-II and insulin receptor levels are the lowest at the end of gestation when the IGF-I levels in foetuses are the highest, when foetal glucose level is the lowest and when foetal GLUT4 expression increases (Hocquette et al, 2006).…”
Section: Endocrine and Metabolic Regulation Of Muscle Physiology Befomentioning
confidence: 99%
“…Assuming a similar trend for the hormonal status in humans and cattle i.e. an increase in IGF-I levels throughout gestation [4] and taking into account the increase in IGF-II plasma levels with increasing age in foetal cattle [53], IGF-I, IGF-II and insulin receptor levels would be low at those stages where IGF-I and placental GH levels in pregnant females and IGF-I levels in foetuses are the highest [4], when foetal glucose level is the lowest and when foetal GLUT4 expression increases (present study). Furthermore, other in vitro studies with cultured cells from the rat hindlimb during differentiation have shown that GLUT1 is abundant in myoblasts, whereas GLUT4 is expressed in spontaneously contracting myotubes but absent in myoblasts [10].…”
Section: Overall Differentiation Of the Heart And Adipose Tissuementioning
confidence: 99%